Development of an online resource for recruitment research in clinical trials to organise and map current literature. (December 2018) - Kearney, Anna; Harman, Nicola L; Rosala-Hallas, Anna; Beecher, Claire; Blazeby, Jane M; Bower, Peter; Clarke, Mike; Cragg, William; Duane, Sinead; Gardner, Heidi; Healy, Patricia; Maguire, Lisa; et al.
Background: Recruiting the target number of participants within the pre-specified time frame agreed with funders remains a common challenge in the completion of a successful clinical trial and addressing this is an important methodological priority. While there is growing research around recruitment, navigating this literature to support an evidence-based approach remains difficult. The Online resource for Recruitment Research in Clinical triAls project aims to create an online searchable database of recruitment research to improve access to existing evidence and to identify gaps for future research. Methods: MEDLINE (Ovid), Scopus, Cochrane Database of Systematic Reviews and Cochrane Methodology Register, Science Citation Index Expanded and Social Sciences Citation Index within the ISI Web of Science and Education Resources Information Center were searched in January 2015. Search strategy results were screened by title and abstract, and full text obtained for potentially eligible articles. Studies reporting or evaluating strategies, interventions or methods used to recruit patients were included along with case reports and studies exploring reasons for patient participation or non-participation. Eligible articles were categorised as systematic reviews, nested randomised controlled trials and other designs evaluating the effects of recruitment strategies (Level 1); studies that report the use of recruitment strategies without an evaluation of impact (Level 2); or articles reporting factors affecting recruitment without presenting a particular recruitment strategy (Level 3). Articles were also assigned to 1, or more, of 42 predefined recruitment domains grouped under 6 categories. Results: More than 60, 000 records were retrieved by the search, resulting in 56, 030 unique titles and abstracts for screening, with a further 23 found through hand searches. A total of 4570 full text articles were checked; 2804 were eligible. Six percent of the included articles evaluated the effectiveness of a recruitment strategy (Level 1), with most of these assessing aspects of participant information, either its method of delivery (33%) or its content and format (28%). Discussion: Recruitment to clinical trials remains a common challenge and an important area for future research. The online resource for Recruitment Research in Clinical triAls project provides a searchable, online database of research relevant to recruitment. The project has identified the need for researchers to evaluate their recruitment strategies to improve the evidence base and broaden the narrow focus of existing research to help meet the complex challenges faced by those recruiting to clinical trials.